ZIF-8@DBzPBI-BuI composite membranes for olefin/paraffin separation - Kunjattu, Shebeeb H.; Ashok, Varsha; Bhaskar, Anand; Pandare, Kiran; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
ZIF-8 is a member of Zeolitic Imidazole Framework family having high internal surface area, the high thermo-chemical stability and ease of synthesis gained immense attention for its highly selective sieving ability. Transforming it into a membrane form and practical utility remains a challenge. Any success towards this direction would radically reduce the cost of propylene/propane separation. Present study reports use of substituted polybenzimidazole (DBzPBI-BuI) for fabrication of flexible, thus scalable composite membranes with ZIF-8 (ZIF8@DBzPBI-BuI) possessing host-guest compatibility. The membrane with 30% ZIF-8 loading showed promising propylene-propane separation (ideal selectivity of 32.7), coupled with propylene permeability of 12.13 Barrer. Analysis of sorption shed light on the high contribution of diffusivity on governing permeation properties of the composite membranes. The mixed gas analysis offered highly encouraging results in comparison to known composite membranes of different polymers with ZIF-8. Placement of present data on `upper-bound' showed a rapid enhancement in selectivity by the addition of ZIF-8 in the polymer matrix, which seems to be a result of the elimination of inter-phase defects. It was made possible due to the functionality of host polymer.
Keywords: Gas permeation; Olefin/paraffin separation; Polybenzimidazole (PBI); ZIF-8